2021
DOI: 10.1039/d1dt00549a
|View full text |Cite
|
Sign up to set email alerts
|

Getting rid of the shackles from the support: construction of recoverable semi-homogeneous catalysts with attapulgite

Abstract: Traditionally, the immobilized catalyst sacrifices a part of catalytic activity for its recyclability. To reproduce the catalytic activity of active specie, we construct a novel strategy called "adsorption-desorption-adsorption". Since the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Compared to these carrier materials, our previous work demonstrated that as a natural nanocatalyst carrier, ATP is more readily available and has excellent CO 2 fixation capacity. 16,17 In addition, it has been demonstrated that the catalytic effect tends to be better when multiple catalyst sites coexist, such as when both metal Lewis acidic sites and Lewis basic sites are included. 18,19 Our group proposes to prepare loaded catalysts using a natural product, attapulgite (ATP), as a carrier to improve the efficiency of the UIO-66 catalyst by using the Lewis alkaline site of ATP pores and Lewis acid sites in the skeleton, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to these carrier materials, our previous work demonstrated that as a natural nanocatalyst carrier, ATP is more readily available and has excellent CO 2 fixation capacity. 16,17 In addition, it has been demonstrated that the catalytic effect tends to be better when multiple catalyst sites coexist, such as when both metal Lewis acidic sites and Lewis basic sites are included. 18,19 Our group proposes to prepare loaded catalysts using a natural product, attapulgite (ATP), as a carrier to improve the efficiency of the UIO-66 catalyst by using the Lewis alkaline site of ATP pores and Lewis acid sites in the skeleton, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%